1996
DOI: 10.1111/j.1574-6968.1996.tb08408.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of bacteria to model solid surfaces: oligo(ethylene glycol) surfaces inhibit bacterial attachment

Abstract: Bacterial cell attachment to the surfaces of self-assembled monolayers formed by the adsorption of omega-substituted alkanethiols on transparent gold films has been studied under defined bacterial culture and flow conditions. Phase contrast microscopy was used to quantify the attachment of two organisms, one of medical (Staphylococcus epidermidis) and one of marine (Deleya marina) importance. Self-assembled monolayers terminated with hexa(ethylene glycol), methyl, carboxylic acid and fluorocarbon groups were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 15 publications
(17 reference statements)
11
81
0
Order By: Relevance
“…Surprisingly, it has also been found that a selfassembled monolayer of PEO with only six PEO units is able to prevent the adhesion of Sta. epidermidis ATCC 14990 and Deleya marina ATCC 25374 (Ista et al, 1996). Bridgett et al (1992) showed that surfactants with PEO chains as short as three PEO units were able to reduce the adhesion of three Sta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, it has also been found that a selfassembled monolayer of PEO with only six PEO units is able to prevent the adhesion of Sta. epidermidis ATCC 14990 and Deleya marina ATCC 25374 (Ista et al, 1996). Bridgett et al (1992) showed that surfactants with PEO chains as short as three PEO units were able to reduce the adhesion of three Sta.…”
Section: Discussionmentioning
confidence: 99%
“…Therewith, a PEO-brush forms a steric barrier preventing close approach and thus attenuates the attractive Lifshitz-Van der Waals interaction between the protein and the surface. PEO-coatings have also been investigated for their ability to prevent bacterial adhesion (Park et al, 1998;Razatos et al, 2000;Ista et al, 1996;Bridgett et al, 1992). Varying results have been obtained, ranging from reductions in bacterial adhesion of 98 % (Razatos et al, 2000;Ista et al 1996), 90-98 % (Bridgett et al, 1992) and between 0 and 90 % (Park et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such inert coatings have been identified for a number of well-defined surfaces in short term, single species assays. Especially ethylene glycol (EG) x -containing coatings have been used in the biomedical area [21][22][23][24] and have recently been investigated with respect to their marine anti-fouling potential [25][26][27][28][29][30][31][32][33]. However, the degradation of the ethylene-glycol-containing chemistries makes them unsuitable for long-term antifouling applications [34,35].…”
Section: Biofouling Research: the Quest For Environmentallymentioning
confidence: 99%
“…Especially self-assembled monolayers (SAM) [75,76] are a versatile class of functional interfaces that are frequently applied in biofouling research, since their mechanical properties are determined by the substrate and thus biological response is solely caused by the surface chemistry. Application of SAM in biofouling research was pioneered by the Lopez group [25,64]. Extensive studies followed, focusing on various surface properties including wettability, hydration, and lubricity [31,33,64,67,77,78].…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of mentioning
confidence: 99%